Surge in Solar-Powered Homes: Experience in Off-Grid Rural Bangladesh - Khandker, ShahidurR. (World Bank, 2015)
Bangladesh has the world's fastest growing, off-grid solar home system (SHS) coverage. In the past decade, the number of SHS installations has risen phenomenally--from a five-year target of 50,000 in 2003 to 50,000 a month in 2013, with support from the World Bank and other development partners. Even so, only 10 percent of off-grid households have been reached, suggesting ample room for continued expansion. Given the recent surge in SHS adoption, a key policy issue is whether the partial subsidy provided under the current program, implemented by the Infrastructure Development Company Limited (IDCOL), should be continued.